Effect of packaging films on storage stability of intermediate‐moisture deep‐fried mackerel - Che Man, Yaakob; Bakar, Jamilah; Mokri, Ahmad A.K (Wiley, 1995)
A storage stability study was conducted on intermediate moisture deep‐fried mackerel packed in polypropylene (PP), high density polyethylene (HDPE) and low density polyethylene (LDPE) for 12 weeks at 27°C. Water activity increased significantly (P < 0.01) during 12 weeks storage from 0.80 to 0.86, 0.88 and 0.91 for PP‐, HDPE‐ and LDPE‐packed samples, respectively. Thiobarbituric acid values increased significantly (P < 0.01) in all packaging films, most rapidly in the LDPE‐packed samples. the physical firmness of the samples decreased similarly and was closely related to the amount of moisture absorbed during storage. Microbial count was low initially but increased most rapidly in LDPE‐packed samples. Sensory evaluation showed that samples packed in PP and HDPE were acceptable for up to 8 weeks storage but for less than 4 weeks in LDPE.